Investigation of a Notable Landslide under Complex Hydrogeological Conditions at Pak Tam Road, Sai Kung, Hong Kong - Lam, Kevin Siu Pang; Tracy, Michael Rudolf (Himpunan Ahli Teknik Tanah Indonesia, 2024)
On 8 June 2022, an intense rainstorm triggered multiple landslides in the northeastern area of Hong Kong. One of these landslides occurred at the registered soil and rock cut slope adjoining Pak Tam Road in the Sai Kung East Country Park with significant social consequences and widespread media attention. An investigation of this notable landslide was undertaken to study the probable causes and mechanism of the failure, as well as the hydrogeological conditions of the slope. The landslide was a large‑scale rain‑induced sliding failure caused by adversely orientated relict joints within the weathered rock profile. Coupling effects of inadequate slope maintenance, steep slope profile and tension cracks rendered the slope particularly vulnerable to landsliding under severe rainfall. Additionally, heavy seepage was observed from some weep holes within the same slope, which suggested the presence of complex hydrogeological conditions. Field mapping and site‑specific ground investigation revealed preferential flow paths along a network of soil pipes and relict joints in the groundmass that prompted the subsurface flow and the build-up of a transient perched groundwater table. The landslide highlighted the importance of proper and regular slope maintenance of slopes in Hong Kong, and the need of assessing the site holistically when modifying the site with engineering works. A robust design solution is strongly advocated for stabilising slopes.